Sugar Beet-Associated Bacterial and Fungal Communities Show a High Indigenous Antagonistic Potential Against Plant Pathogens - Zachow, Christin; Tilcher, Ralf; Berg, Gabriele (Microbial ecology, 2008)
The aim of this study was to analyze microbial communities in/on sugar beet with special focus on antagonists toward plant pathogens. For this purpose, the composition of microorganisms isolated from the rhizosphere, phyllosphere, endorhiza, and endosphere of field-grown sugar beet plants was analyzed by a multiphasic approach at three different plant development stages at six locations in Europe. The analysis of microbial communities by Single Strand Conformation Polymorphism (SSCP) of 16S/18S rRNA clearly revealed the existence of discrete microenvironment- and site-specific patterns. A total of 1952 bacterial and 1344 fungal isolates screened by dual testing for antagonism toward the pathogens Aphanomyces cochlioides, Phoma betae, Pythium ultimum, and Rhizoctonia solani resulted in 885 bacterial (=45%) and 437 fungal (=33%) antagonists. In general, the indigenous antagonistic potential was very high and influenced by (a) the location, (b) the plant developmental stage, and (3) the microenvironment. Furthermore, we showed for the first time that the antagonistic potential was highly specific for each target pathogen. The majority of antagonistic microorganisms suppressed only one pathogen (bacteria: 664 = 75%; fungi: 256 = 59%), whereas the minority showed a broad host range (bacteria: 4 = 0.5%; fungi: 7 = 1.6%). The bacterial communities harbored the highest antagonistic potential against P. ultimum, whereas the fungal communities contained more antagonists against A. cochlioides and R. solani. In contrast to their high proportion, only a low diversity of antagonists at genotypic and species level was found. Novel antagonistic species, e.g., Subtercola pratensis or Microbacterium testaceum were found in the internal part of the sugar beet body.